Analisis Aktivitas, Likuiditas, dan Solvabilitas terhadap Profitabilitas pada Perusahaan Minuman dan Makanan di Bursa Efek Indonesia (BEI) Periode 2017-2021 - Ni Wayan Puja Lestari; Ni Luh Kardini; Komang Asri Pratiwi (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
This research was conducted in the Food and Beverage sector companies listed on the Indonesia Stock Exchange during the period 2017-2021 with the title "Analysis of Activity, Liquidity, and Solvency on Profitability in Food and Beverage Companies Listed on the Indonesia Stock Exchange (IDX) Period 2017-2021." The data used in this study is quantitative data from secondary sources. The sample was selected using purposive sampling based on specific criteria, with 27 companies selected as samples, making a total of 135 companies studied from the period 2017-2021. The research technique used was multiple linear regression analysis.Partially, the findings of this research state that: 1) Activity has a positive and significant effect on profitability, indicated by a significant value of 0.052 ≤ 0.05 and a t-value of 1.963 > 1.65648. 2) Liquidity has a positive and significant effect on profitability, with a significant value of 0.044 ≤ 0.05 and a t-value of 2.038 > 1.65648. 3) Solvency has a positive and significant effect on profitability, with a significant value of 0.000 ≤ 0.05 and a t-value of 18.944 > 1.65648. 4) Simultaneously, activity, liquidity, and solvency have a positive and significant effect on profitability, as indicated by a significant value of 0.000 < 0.05 and an F-value of 147.949 > 3.07. The determination test shows that 76.7% of the variations in activity, liquidity, and solvency affect profitability, while 23.3% (100% - 76.7%) is influenced by other factors beyond the independent variables studied in food and beverage companies listed on the IDX from 2017 to 2021.